Transversus Abdominis Plane Block: A Cadaveric and Radiological Evaluation. Issue 5 (1st September 2007) - McDonnell, John G.; O'Donnell, Brian D.; Farrell, Thomas; Gough, Niall; Tuite, David; Power, Camillus; Laffey, John G.
Abstract : Background and Objectives: The abdominal wall is a significant source of pain after abdominal surgery. Anterior abdominal wall analgesia may assist in improving postoperative analgesia. We have recently described a novel approach to block the abdominal wall neural afferents via the bilateral lumbar triangles of Petit, which we have termed a transversus abdominis plane block. The clinical efficacy of the transversus abdominis plane block has recently been demonstrated in a randomized controlled clinical trial of adults undergoing abdominal surgery. Methods: After institutional review board approval, anatomic studies were conducted to determine the deposition and spread of methylene blue injected into the transversus abdominis plane via the triangles of Petit. Computerized tomographic and magnetic resonance imaging studies were then conducted in volunteers to ascertain the deposition and time course of spread of solution within the transversus abdominis fascial plane in vivo. Results: Cadaveric studies demonstrated that the injection of methylene blue via the triangle of Petit using the "double pop" technique results in reliable deposition into the transversus abdominis plane. In volunteers, the injection of local anesthetic and contrast produced a reliable sensory block, and demonstrated deposition throughout the transversus abdominis plane. The sensory block produced by lidocaine 0.5% extended from T7 to L1, and receded over 4 to 6 hours, and this finding was supported by magnetic resonance imaging studies that showed a gradual reduction in contrast in the transversus abdominis plane over time. Conclusions: These findings define the anatomic characteristics of the transversus abdominis plane block, and underline the clinical potential of this novel block.